The Effectiveness of Educational Care in Psychosocial Rehabilitation For Children with Mental Disabilities: A field Study at the Psychological Center in Busaada - saoud, fatima; fourchan, louiza (Journal of Social Sciences and Humanities, 2019)
Mental disability is one of the social issues of educational and economic dimensions that has become the focus of attention of all societies alike. The mental disability is not only a burden on the disabled and his family, but its effects extend to various institutions of society, as these disabled people need special care in all respects, psychological, social and educational ..., not to mention the financial expenses resulting from such care Special equipment, medicines and medical and psychological follow-up are ongoing; therefore, in the second half of the last century, many countries have enacted laws and legislation that determine the responsibility of society towards individuals with disabilities. Nevertheless, the care and maintenance of this category of society remains a human, moral and religious duty, with the sole purpose of alleviating the mental disability to the life of its owner, and to enable it to improve its harmony with itself & its community. Therefore, the present study aimed to reveal the effectiveness of educational care from the psychological & social aspects provided by mothers to rehabilitate mentally handicapped children in the psychiatric center in Bou Saada / Algeria, in addition to knowing whether there are statistically significant differences in the level of educational care for mothers of children with mental disabilities in the psychosocial rehabilitation of their children. To the variables (age, educational level, number of children, degree of disability), and to achieve the objectives of the study was developed a questionnaire to collect data, applied to a sample of (116) mother of a child with a mentally disabled. The study reached a number of results, the most important of which are: the presence of statistically significant differences in the level of educational care for the mothers of mentally handicapped children for the psychosocial rehabilitation of their children due to the age variable; and the absence of statistically significant differences in the level of educational care for the mothers of the mentally handicapped children in the psychosocial rehabilitation of their children due to variables (educational level , number of children, degree of disability). In the light of these findings, the study recommended increasing attention to the family of the mentally handicapped child through the provision of training and guidance programs to educate parents on the effectiveness of methods of caring for the mentally handicapped child in the psychological, social and educational field.